2022
DOI: 10.5114/pedm.2022.116111
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile obesity in terms of various evaluation methods

Abstract: Introduction: Obesity is a civilization disease of the 21 st century. The prevalence of obesity and overweight among children and adolescents is constantly increasing. BMI (body mass index) and WHR (waist to hip ratio) are methods of obesity assessment recommended by the WHO. Also, the WtHR (waist to height ratio), which takes into account height, is one of the most popular methods of diagnosing childhood obesity. A more recent diagnostic indicator is the FMI (fat mass index), which considers the percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…It is important to note that in the IDF criteria of MetS, WC>90th percentile is used as a marker of abdominal obesity, not BMI ( 8 ). Therefore, alternative screening tests to assess obesity in childhood and adolescence have been suggested as being superior to BMI in predicting CVD risks such as waist-to-height ratio (WHtR) and waist-to-hip ratio (WHR) ( 10 , 35 , 36 , 56 ). The WHR as a marker of abdominal obesity was approved by WHO for adults without age restrictions and with high sensitivity in young people ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that in the IDF criteria of MetS, WC>90th percentile is used as a marker of abdominal obesity, not BMI ( 8 ). Therefore, alternative screening tests to assess obesity in childhood and adolescence have been suggested as being superior to BMI in predicting CVD risks such as waist-to-height ratio (WHtR) and waist-to-hip ratio (WHR) ( 10 , 35 , 36 , 56 ). The WHR as a marker of abdominal obesity was approved by WHO for adults without age restrictions and with high sensitivity in young people ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cutoff value, which is age and gender independent, is above 0.5 ( 36 ). The debate is still ongoing on whether WHR and WHtR are criteria for obesity in general or abdominal obesity as a separate type ( 56 ). The results of our study showed that WHtR and WHR are significantly higher in subjects with MUO and MetS than in those with MHO and the control group, which might indicate a higher risk of CVD as it was recognized in other studies ( 10 , 53 , 57 ).…”
Section: Discussionmentioning
confidence: 99%